LINKING METAL EXPOSURE TO ISCHAEMIC HEART DISEASE: A BIOINFORMATIC ANALYSIS - Fuat Karakuş; Burak Kuzu (Sabiad)
Objective: Cardiovascular disease causing the most deaths worldwide is ischaemic heart disease. In addition to modifiable and non-modifiable risk factors, there is a growing consideration that environmental factors, especially heavy metals, may also contribute to the risk of ischaemic heart disease. The study identified the potential molecular mechanisms associated with ischaemic heart disease induced by arsenic, cadmium, lead, and mercury. Materials and Methods: In this study, we used toxicogenomic data and various bioinformatic databases and tools, including the Comparative Toxicogenomic Database, ToppGene Suite, GeneMANIA, String, Cytoscape, CHEA3, and MIENTURNET. Results: We observed an overlap of the CRP, HMOX1, PON1, and PTGS2 genes among the metals and ischaemic heart disease. The most prevalent interactions among these genes were identified as physical interactions, constituting 77.64% of the total. Several pathways were determined as the principal molecular mechanisms that might be influenced by the examined metals involved in the aetiology of ischaemic heart disease (e.g., regulation of plasma lipoprotein particle levels, response to inorganic substances, blood circulation, circulatory system processes, and cellular response to metal ions). CRP and HMOX1 emerged as key genes, whereas CREB3L3 and ATF5 were identified as key transcription factors related to ischaemic heart disease caused by the combination of the examined metals. Furthermore, we identified two miRNAs (hsa-miR-128-3p and hsa miR-1273g-3p) associated with ischaemic heart disease.Conclusion: These observations make a substantial contribution to our understanding of the processes underlying ischaemic heart disease induced by arsenic, cadmium, lead, and mercury.